Analisis Faktor Yang Mempengaruhi Rendahnya Minat Penggunaan Kontrasepsi Implan - Rizki Amalia; Adelia Lestari; Adelia Vannesa (PT Nuansa Fajar Cemerlang, 2026)
The use of long-acting reversible contraceptives (LARC), particularly implants, remains low despite their high effectiveness. This study aimed to analyze factors influencing the low interest in implant contraceptive use at Celikah Public Health Center. This research used a quantitative method with a cross-sectional design involving 305 respondents selected through proportional random sampling. Data were collected using structured questionnaires and analyzed using the Chi-square test. The results showed that 62.3% of respondents had low interest in using implant contraception. There was a significant relationship between knowledge (p=0.001), husband support (p=0.000), and fear of side effects (p=0.000) with interest in implant use. Respondents with low knowledge, lack of husband support, and high fear of side effects were more likely to have low interest. In conclusion, knowledge, husband support, and fear of side effects significantly influence the interest in using implant contraception. It is recommended to strengthen education and involve husbands in family planning programs.